2019
DOI: 10.1111/ans.15005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic symmetry of anterolateral thigh flap perforators: a computed tomography angiographic study

Abstract: Background: The anterolateral thigh flap is a workhorse reconstructive flap. Versatility in design is a key strength but perforator anatomy can be variable. Inability to locate perforators prompts consideration of contralateral thigh exploration. However, such exploration would be futile if the absence of perforators proves symmetrical. This study assesses the symmetry of anterolateral thigh flap vasculature using computed tomography angiography (CTA). Methods: A retrospective analysis of 20 bilateral thigh CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We also identified a high rate of dominant perforator asymmetry between lower extremities in 32 patients (40.5%), a finding shared by several anatomic studies. 7 8 This is particularly important when there may be extreme differences in perforator anatomy between each side. There were 10 (12.7%) patients who entirely lacked visualized perforators on one side, and we theoretically avoided a poor operative course by seeing this on imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified a high rate of dominant perforator asymmetry between lower extremities in 32 patients (40.5%), a finding shared by several anatomic studies. 7 8 This is particularly important when there may be extreme differences in perforator anatomy between each side. There were 10 (12.7%) patients who entirely lacked visualized perforators on one side, and we theoretically avoided a poor operative course by seeing this on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous cadaveric and imaging studies have shown substantial intra- and interlimb perforator asymmetry within individual patients 7 8 and among individuals of different races and ethnicities. 9 10 11 Studies have revealed between one to four perforators emerge from the dbLFCA around the midpoint between the anterior superior iliac spine and the lateral patellar border.…”
mentioning
confidence: 99%
“…Identification of the ALT and MSAP vessels followed previously described techniques, [15][16][17]19 which were also applied for identifying PB vasculature. Axial two-dimensional images were scanned craniocaudally using our institution's standard CT image viewing software, Merge Radsuite (Merge Healthcare, Hartland, Wis.).…”
Section: Image Analysismentioning
confidence: 99%
“…As described by Lu et al 13 , the perforator arteries of LCFA were located with a hand-held Doppler probe. The size and shape of the flap was planned based on the size and shape of the defect, and marked by more than 1 to 2 cm larger than the desired flap size.…”
Section: Flap Designmentioning
confidence: 99%